PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Ahmad Alawiy (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2015)
Cooperative learning model Team Assisted Individualization is one approach that helps students to solve a creative problem-solving. The research was conducted at SMK NU Gresik. With the research subjects were students of class X MM SMK NU Gresik This study uses two cycles that each cycle has four stages: planning, implementation, observation phase, and the phase of reflection. Data collection method used is to use a subjective test in every cycle. Data in the form of student test results will then be analyzed descriptively to determine student mastery of learning outcomes in the classical style. From the results of the research activities that have been carried out for two cycles, and based on the discussion and analysis that has been carried out can be concluded that the application of cooperative learning model Team Assisted Individualization (TAI) to improve learning outcomes quadratic equation mathematics subject in class X-MM SMK NU Gresik 2012-2013 school year. It can be seen from the improvement of student learning in the classical mastery of each cycle, the prasiklus 57.5% to 72.5% in the first cycle, but has yet to achieve mastery in the classical learning. Then the deficiencies in the first cycle improvements held on the second cycle increased 87.5% to reach 15% of cycle I. In the second cycle students have achieved mastery in the classical so expect the teachers to consider using this learning model Keywords: Team Assisted Individualization, mathematics learning achievements, quadratic equation